2003
DOI: 10.1091/mbc.e02-08-0544
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-like Ox-LDL Receptor Is Expressed in Human INT-407 Intestinal Cells: Involvement in the Transcytosis of Pancreatic Bile Salt–dependent Lipase

Abstract: We have recently shown that the pancreatic bile salt-dependent lipase (BSDL) can be taken up by intestinal cells and transported to the blood circulation. This mechanism likely involves (specific) receptor(s) able to bind BSDL and located at the apical intestinal cell membrane. In this study, using Int407 human intestinal cells cultured to form a tight epithelium, we attempted to characterize (the) BSDL receptor(s). We found that an apical 50-kDa protein was able to bind BSDL. Further, we have demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…This heterogeneity may also be responsible for fluctuations in our quantitative results particularly evident for lipase over the endosomal compartment ( Figure 9B). Previous studies on BSDL have identified a receptor, LOX-1, located at the enterocyte luminal membrane responsible for its internalization (Bruneau et al 2003b). This finding entails internalization of BSDL as a rather specific event, and some cells may be more prone than others.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity may also be responsible for fluctuations in our quantitative results particularly evident for lipase over the endosomal compartment ( Figure 9B). Previous studies on BSDL have identified a receptor, LOX-1, located at the enterocyte luminal membrane responsible for its internalization (Bruneau et al 2003b). This finding entails internalization of BSDL as a rather specific event, and some cells may be more prone than others.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, BSDL, in concert with other digestive lipolytic enzymes, degrades dietary lipids and participates in the hydrolysis of cholesterol esters into free cholesterol and fatty acids (6). In the duodenum, a fraction of BSDL is internalized by enterocytes via the lectin-like oxidized LDL receptor (LOX-1) and transported to the blood compartment (7,8), where it partly associates with apolipoprotein B-containing lipoproteins in plasma (6). The concentration of circulating BSDL in human serum, determined by ELISA using polyclonal antibodies, is 1.5 ± 0.5 μg/l (9-11) but is elevated to a level as high as 7 μg/l in some pathological conditions, such as acute pancreatitis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are conflicting reports, the enzyme may be synthesized by macrophages and endothelial cells (14,15). Alternatively, BSDL, which has a heparin-binding site (16) and a V3-like loop domain (17), associates with intestinal cell-surface proteoglycans (7,8). In vitro studies have shown that BSDL induces vascular smooth muscle cell proliferation and evokes endothelial cell proliferation and chemotactic migration (13,18).…”
Section: Introductionmentioning
confidence: 99%
“…LOX-1 is expressed on the main cells involved in atherogenesis as well as on the plaques themselves. 56 Although LOX-1 is located on a number of non-vascular cells such as chondrocytes and intestinal cells, 15,57 it is not as widely expressed as other scavenger receptors such as Cluster of Differentiation 36 (CD36). It is therefore an attractive target for the development of selective drug delivery systems.…”
Section: Lox-1 As a Target For The Selective Delivery Of Drugsmentioning
confidence: 99%